2023
DOI: 10.1071/fp22294
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of plant tissue O2 dynamics

Abstract: Adequate tissue O2 supply is crucial for plant function. We aimed to identify the environmental conditions and plant characteristics that affect plant tissue O2 status. We extracted data and performed meta-analysis on >1500 published tissue O2 measurements from 112 species. Tissue O2 status ranged from anoxic conditions in roots to >53 kPa in submerged, photosynthesising shoots. Using information-theoretic model selection, we identified ‘submergence’, ‘light’, ‘tissue type’ as well as ‘light × submergenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Due to the gas exchange constraints imposed by flooding, many studies have examined tissue O 2 status in partially or completely submerged plant tissues. A recent meta-analysis of >500 studies and encompassing 112 species showed that O 2 status ranged from effectively 0 kPa in roots to >50 kPa in submerged, photosynthesizing shoots ( Herzog et al , 2023 ). When flooded, tissue O 2 status was particularly low in rhizomes, potato tubers, and root nodules.…”
Section: Determining O 2 In Flooded Habitats and I...mentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the gas exchange constraints imposed by flooding, many studies have examined tissue O 2 status in partially or completely submerged plant tissues. A recent meta-analysis of >500 studies and encompassing 112 species showed that O 2 status ranged from effectively 0 kPa in roots to >50 kPa in submerged, photosynthesizing shoots ( Herzog et al , 2023 ). When flooded, tissue O 2 status was particularly low in rhizomes, potato tubers, and root nodules.…”
Section: Determining O 2 In Flooded Habitats and I...mentioning
confidence: 99%
“…Surprisingly, root O 2 status is not influenced by light or darkness as long as the shoot is exposed to air due to the effective O 2 exchange between the shoots and the atmosphere ( Herzog et al , 2023 ). However, measurements using miniaturized Clark-type O 2 sensors ( Revsbech, 1989 ) show that the stele operates at a significantly lower O 2 tension than the cortex, even in roots acclimated to soil flooding ( Herzog et al , 2023 ).…”
Section: Determining O 2 In Flooded Habitats and I...mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the availability of molecular O 2 can restrict underwater respiration of submerged terrestrial plants, and an O 2 pressure of almost twice that of atmospheric equilibrium is needed to saturate respiration ( Colmer and Pedersen, 2008 ). A recent meta-analysis encompassing 112 species of both aquatic and terrestrial plants have clearly demonstrated that partial or complete submergence lead to significant declines in tissue O 2 status particularly during darkness when the only source of O 2 for underwater respiration is O 2 dissolved in the floodwater ( Herzog et al., 2023 ). However, some species of wetland plants form numerous adventitious roots emerging from the stem and hanging into the floodwater as response to partial or complete submergence ( Rich et al., 2013 ; Zhang et al., 2017 ; Lin et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…The efficient supply of oxygen to the roots involves considering the characteristics of the above-ground parts as an oxygen supply source and the roots as a sink [ 8 , 13 ]. A meta-analysis integrating 129 studies on tissue oxygen concentrations in plants demonstrated longitudinal oxygen diffusion from the leaves to the roots [ 14 ]. Additionally, evidence from noninvasive methods using N-isotopes showed leaf-to-root gas diffusion in partially submerged rice plants [ 15 ].…”
Section: Introductionmentioning
confidence: 99%